Mental health consumer and caregiver perceptions of stigma in Australian community pharmacies - Knox, K.; Fejzic, J.; Mey, A.; Fowler, J.; Kelly, F.; McConnell, D.; Hattingh, H. Laetitia; Wheeler, A. (Sage Publications Ltd., 2014)
Background: The stigma of mental illness can be a barrier to effective medication management in the community pharmacy setting. This article explored mental health consumers’ or caregivers’ experiences of stigma in Australian community pharmacies. Materials: Semi-structured interviews and focus groups were conducted with a purposive sample of consumers or caregivers (n = 74). Interview transcripts were analysed using a general inductive approach. Discussion: Stigma presented a barrier to effective mental health management. Self-stigma impeded consumers’ community pharmacy engagement. Positive relationships with knowledgeable staff are fundamental to reducing stigma. Conclusions: Findings provide insight into the stigma of mental illness in community pharmacies.